Avaliação da coordenação do cuidado das equipes de atenção básica: uma análise a partir do Programa de Melhoria do Acesso e da Qualidade da Atenção Básica - Miriam Francisco de Souza (2015)
The economic, social, cultural and political alterations occurring worldwide brought changes in the epidemiological and demographic profile of the population. To accompany these changes, health systems put Primary Health Care (APS) in the coordination of care. In Brazil, the National Program for Access and Quality Improvement in Primary Care (PMAQ AB) presents itself as a quality improvement strategy of the APS assistance since 2012. The Ministry of Health puts the challenge of the establishment of the Family Health Strategy as center of Health Care Networks in ordering and coordination of care. The study aimed to assess the quality of National Program for Access and Quality Improvement in Primary Cares variables (PMAQ-AB) to evaluate primary care as coordinator of care in Brazil. This was a cross-sectional study based in Item Response Theory (IRT), with PMAQ-ABs data collected in 2012. The study included 17202 primary care teams. The Samejimas Gradual Response Model was used to estimate the parameters of the items and the score related to the level of coordination. The Cronbach's alpha and the Spearmans coefficient were used to analyze the internal consistency and the correlation between the items and the total score. Assessed the assumptions of unidimensionality and independence of the items. The word clouds graph helped in interpreting the levels of coordination. The results showed that the items with greater discrimination of the coordination level were the existence of telephone/internet, institutional communication flows and matrix support actions. The frequency of experts contact with primary care professionals and integrated electronic medical records demanded higher level of coordination of teams. The total Cronbachs alpha of the items was 0.8018. Institutional communication flows had higher correlation with the total score. The coordination scores ranged from -2.673 (minimum) and 2.835 (maximum). The assumption of unidimensionality considered valid. A greater degree of communication, information exchange, matrix support, care in the home and territory had a relevant weight in coordination levels. It was concluded that the ability to make the information available and the frequency of contact between professionals are important elements for comprehensive care, continuous and quality.